Dampak Metode Penyuluhan Langsung dan Tidak Langsung Terhadap Peningkatan Keterampilan Kelompok Tani Hortikultura Kecamatan Ruteng - Jandu, Inosensius Harmin; Utama, Wigbertus Gaut (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
For progress in agriculture, farmers as the main actors need increased resources. They must be able and have the skills to run their business, and extension workers as motivators must use effective methods to influence the farming community. Capabilities can be improved through learning processes, effective training and agricultural extension. The aim of this research is the direct and indirect impact of extension on farmers' skills in Ruteng District, Manggarai Regency. Time and Place of Research This research was conducted in Ruteng District, Manggarai Regency. Data collection was carried out on 10 August-10 October. In an effort to answer the problems in this research, multiple linear regression analysis was used. The author of this research used a quantitative descriptive approach. Based on the research results, it can be concluded that: The direct extension method has a positive and significant effect on farmers' skills and the indirect method has a positive but not significant effect on farmers' skills in Ruteng District, Manggarai Regency. The direct method is used when agricultural instructors face the target and obtain a response from the target in a relatively short time, while the indirect method is used when the instructor uses extension media and does not meet directly with the target to obtain a response. This second method can be very helpful in situations where direct methods cannot be used, especially in terms of attracting attention and moving the hearts of the target instructor.